Winds of change Book Two of the Mage Winds - Lackey, Mercedes (DAW Books New York, 1994)
With Valdermar in dire peril, Princess Elspeth, Herald and heir to the throne, has come to the Vale of the Tayledras Clan to seek Mage training among the magical Hawkbrother Adepts. But instead of finding a haven she is whirled into war and sorcery as the Vale is attacked by a mysterious Dark Adept from out of the "Uncleansed Lands".
94613
Keywords: Science fiction; Fantasy